Mengembangkan Kemampuan Motorik Halus Anak Menggunakan Kombinasi Model Pbl Model Explicit Instruction Melalui Permainan Tradisional Dakuan Di Kelompok B TK Negeri Pembina Banjarmasin Timur - Fradya Auriani; Mohammad Dani Wahyudi (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study was to describe teacher activities, analyze children's activities, and analyze the results of children's fine motor skill development. This study used a qualitative approach with Classroom Action Research (CAR) conducted over four meetings. The subjects were 15 children in Group B at Pembina State Kindergarten, East Banjarmasin. The results showed that teacher activities were in the “Very Good” category with a score of 26. Children's activities were in the “Very Active” category with a score of 100%. The results of children's fine motor development were in the